FALSAFAH HIDUP PEREMPUAN JAWA - Sulastri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Woman are endless material for conversation. Woman, on the one hand are often described as weak, helpless and inferior. On the other hand, (sometimes) woman have the power to subjugate men and that strength is certainly not physical strength, because physically, women are indeed weaker than men. This article is an attempt to outline the life philosophy of Javanese women and is interpreted as an alternative concept for the position of woman today.